Kajian Teori Behavioristik pada Media Pembelajaran Flipbook - Amanah Surbakti; Shafisiyah Adya Larasati; Trisni Adelia; Mardiansyah Mardiansyah; Dinda Saranisah Putri; Iklil Nabila Hayati (Universitas Batanghari Jambi, 2023)
In this study the aim was to examine a behavioristic theory on flipbook learning media. The data collection technique used is a library research method by collecting primary and secondary data. Primary data here uses the theory of several behaviorists and secondary data in the form of scientific articles and books from various sources. From several studies and literature that have been processed by researchers, it can be concluded that another impact of behavioristic theory includes the birth of mastery learning formulas, which emphasize thorough learning. Complete learning has implications for the development of learning media, good learning media is one that can provide completeness in learning, meaning how learning is conditioned in such a way from the beginning to the end of learning, with clear and structured stages and steps, therefore in development the media needs to have a flowchart as an illustration in the development of learning media. The use of flowcharts is part of the influence of behaviorism learning theory. Another form of influence from the theory of behaviorism is programmed learning and individual teaching. Learning media is a highly programmed and individual form of learning. That's why learning design is very important as part of learning conditioning efforts. Likewise the presentation of material, giving summaries, questions and feedback are also part of the effort to provide stimulus, condition, know the response in learning.